LONGER‐RUN EFFECTS OF ANTI‐POVERTY POLICIES ON DISADVANTAGED NEIGHBORHOODS. (29th September 2019) - Neumark, David; Asquith, Brian; Bass, Brittany
Abstract : We assess evidence on the longer‐run effects of minimum wages, the Earned Income Tax Credit, and welfare on key economic indicators of economic self‐sufficiency in disadvantaged neighborhoods. The evidence suggests that the longer‐run effects of the Earned Income Tax Credit are to increase employment and to reduce poverty and public assistance. We also find some evidence consistent with higher welfare benefits having longer‐run adverse effects, and stronger evidence that tighter welfare time limits reduce poverty and public assistance in the longer‐run. The evidence on the longer‐run effects of the minimum wage on poverty and public assistance is not robust. ( JEL J22, J23, J38)